Essential role of M1 macrophages in blocking cytokine storm and pathology associated with murine HSV-1 infection. - Ujjaldeep Jaggi (Public Library of Science (PLoS), 2021)
Ocular HSV-1 infection is a major cause of eye disease and innate and adaptive immunity both play a role in protection and pathology associated with ocular infection. Previously we have shown that M1-type macrophages are the major and earliest infiltrates into the cornea of infected mice. We also showed that HSV-1 infectivity in the presence and absence of M2-macrophages was similar to wild-type (WT) control mice. However, it is not clear whether the absence of M1 macrophages plays a role in protection and disease in HSV-1 infected mice. To explore the role of M1 macrophages in HSV-1 infection, we used mice lacking M1 activation (M1-/- mice). Our results showed that macrophages from M1-/- mice were more susceptible to HSV-1 infection in vitro than were macrophages from WT mice. M1-/- mice were highly susceptible to ocular infection with virulent HSV-1 strain McKrae, while WT mice were refractory to infection. In addition, M1-/- mice had higher virus titers in the eyes than did WT mice. Adoptive transfer of M1 macrophages from WT mice to M1-/- mice reduced death and rescued virus replication in the eyes of infected mice. Infection of M1-/- mice with avirulent HSV-1 strain KOS also increased ocular virus replication and eye disease but did not affect latency-reactivation seen in WT control mice. Severity of virus replication and eye disease correlated with significantly higher inflammatory responses leading to a cytokine storm in the eyes of M1-/- infected mice that was not seen in WT mice. Thus, for the first time, our study illustrates the importance of M1 macrophages specifically in primary HSV-1 infection, eye disease, and survival but not in latency-reactivation.